Identifikasi Identitas Lokal pada Bangunan Pusat Seni dan Budaya sebagai Upaya Pelestarian Arsitektur - Ivanka, Tia; Avenzoar, Azkia (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
One aspect of culture, art is an important part that must continue to develop from time to time. Art is an integral part of human history and civilization. In the current era og globalization, arts and cultural center facilities are important in every region of Indonesia because they can influence the younger generation and artists to appreciate and love local art and culture. The application of local cultural identity in architectural design and interior design is very important, because it aims to introduce regional characteristics and differentiate it from other buildings. This aim of this research is to analyze local identity presented in arts and culture center buildings as an effort to preserve local culture or identity. This research uses a descriptive method with a qualitative approach with a case study method. This research takes a case study covering 2 objects, namely the Yogyakarta Cultural Park and the Radjawali Semarang Cultural Center Building. So the data was collected through literature study, observation and interviews. The research results show that by presenting local identity at the arts and culture center as an educational facility the aim is to preserve local arts and culture and commemorate the history of the building. In addition, by presenting local identity in the architectural form of these two objects, it shows the differences and uniqueness of each in promoting and preserving local arts and culture.